Desiccation survival times in different desiccation-tolerant plants - Benkő, Zsuzsanna (Acta Biologica Szegediensis, 2002)
There is not exact information on the longevity of the desiccated period after what the desiccation tolerant plants can recover their photosynthetic structure and function. Generally , the longer the period spent in a desiccated state the less is the potential to full metabolic recovery. We know just that vascular DT-s can survive longer desiccated periods than cryptogams. Therefore, in the case of three cryptogam DT species: the moss Tortula ruralis, and the lichens Cladonia convoluta, an d C. furcata, and two vascular monocotyledonous DT species: Xerophyta scabrida, and Coleochloa microcephala were examined the recovery of their net C02 assimilation during rehydration (following stored in dry stage for different lengths). According to our results the cryptogams were able to recover their photosynthetic activity just after 4 months or less, while the leaves of X. scabrida an d C. microcephala remained able to revive afte r2-11 years of desiccation.